Differential diagnosis of gout and tenosynovial giant cell tumor, a case report - P. I. Pyatnitskaya; E. N. Otteva; E. V. Polukhina (Современная ревматология, 2025)
Gout is the most common inflammatory joint disease, related to microcrystalline arthritis. With improper or inadequate treatment, gout can lead to disability.A patient with a misdiagnosis of tophaceous gout is described in whom a differential diagnosis with a neoplasm was performed. As a result of the additional examination, a giant cell tenosynovial tumor of the second finger of the right hand was discovered.